2014
DOI: 10.1007/s10646-014-1259-x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and depuration of gold nanoparticles in Daphnia magna

Abstract: This study presents a series of short-term studies (total duration 48 h) of uptake and depuration of engineered nanoparticles (ENP) in neonate Daphnia magna. Gold nanoparticles (Au NP) were used to study the influence of size, stabilizing agent and feeding on uptake and depuration kinetics and animal body burdens. 10 and 30 nm Au NP with different stabilizing agents [citrate (CIT) and mercaptoundecanoic acid (MUDA)] were tested in concentrations around 0.5 mg Au/L. Fast initial uptake was observed for all stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
2

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 34 publications
6
48
0
2
Order By: Relevance
“…The depuration rate constants (k e ; Table 2) of QEI (0.0057/h) and of QSH (0.0079/h) were lower than QSA (0.0189/h). Similar uptake and elimination patterns were observed when exposed to Au NP (Skjolding et al, 2014). Slow depuration kinetics were calculated (0.02-0.26/h) and were highly dependent on not only surface properties but also particle sizes.…”
Section: Elimination Of Qds From D Magnasupporting
confidence: 61%
“…The depuration rate constants (k e ; Table 2) of QEI (0.0057/h) and of QSH (0.0079/h) were lower than QSA (0.0189/h). Similar uptake and elimination patterns were observed when exposed to Au NP (Skjolding et al, 2014). Slow depuration kinetics were calculated (0.02-0.26/h) and were highly dependent on not only surface properties but also particle sizes.…”
Section: Elimination Of Qds From D Magnasupporting
confidence: 61%
“…At 24 h, the bulk of the nanoparticle body burden was present in the tail region, indicating rapid removal irrespective of food availability. Both Skjolding et al and Khan et al identified fast removal of gold citrate nanoparticles in the first few hours followed by a slower elimination in the presence of a food source. Interestingly, in these studies elimination from the slow compartment proceeded at least an order of magnitude more slowly than we observed, highlighting the sensitivity of elimination to differences in food source, water quality, and organism origin.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, concentration at steady state can be predicted with kinetic constants that are species specific and are adaptable to variable exposure conditions [20]. Several studies used the kinetic approach to predict nanoparticle accumulation [4,5,8,[21][22][23][24], but few have sought to describe the effect of nanoparticle characteristics on biodynamic rate constants for uptake and elimination [21,24].…”
Section: Introductionmentioning
confidence: 99%
“…Since CuO nanoparticles are only taken in by ingestion (as indicated below; copper salt may be taken in by additional mechanisms), a trade-off may occur between ingestion of algae and ingestion of nanoparticles. Similarly, Skjolding et al (2014) indicates that when fed on algae, the uptake of gold nanoparticles by D. magna is less efficient than when not fed. The high copper concentrations in the nanoparticle exposure and the electron microscopic study indicate that the nanoparticle aggregates are ingested by the daphnids and can be localized in the gut lumen but do not appear to penetrate the cells.…”
Section: 2mentioning
confidence: 99%